A Promoter of Italian Language and Culture in Iceland: Þórhallur Þorgilsson - Barindi, Mauro (Nordicum-Mediterraneum, 2006)
Whenever one wishes to sketch an overview of the presence of Italian language and culture in the Nordic countries, Iceland stands out as the nation where Italian studies have hardly ever established firm roots and blossomed into a solid scholarly tradition. Amongst the few to have contributed to making this presence less ephemeral, also and especially at the institutional level, is Þórhallur Þorgilsson.